Tinjauan Akidah Islam terhadap Adat Mappalili di Balla Lompoa Kelurahan Baju Bodoa Kecamatan Maros Baru Kabupaten Maros Sulawesi Selatan - Nuraeni Novira; Auliani Ahmad (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2019)
This study aimed to know: (1) the form of the tradition of Mappalili in Balla Lompoa, Baju Bodoa, Maros Baru District, Maros Regency; (2) community’s response to the tradition of Mappalili in Balla Lompoa, Baju Bodoa, Maros Baru District, Maros Regency; and (3) viewpoint of Islamic faith on the tradition of Mappalili in Balla Lompoa, Baju Bodoa, Maros Baru District, Maros Regency. The type of research was descriptive-qualitative, that was to understand the phenomena or occurrences regarding the tradition performed by research subjects that resulted descriptive data in the form of oral information from some people who were considered to know better, and behaviors and observed objects. The result of the study shows that: (1) the tradition of Mappalili is a series of unique traditional ceremonies of Karaeng Marusu which essentially implies the make-use of royal tools in the royal rice field which was named Turannu to plow the rice field area using the relic of Pajekkona Karaenga ri Marusu which is conducted traditionally; (2) good responses of community to the traditional ritual of Mappalili is excessive, they still orient themselves, and the people who work on the rice fields and farmer groups make agreement with the rice field owners on that they are not to start the activities of working on their fields before the traditional ritual of Mappalili is held; (3) Traditional ritual of Mappalili and all of its series of events, including pa'jeko, beating drums with its accompaniment, prayers, and wishes of this party are against the monotheism in terms of Rububiyah and Uluhiyah.